DFT insight into the adsorption behavior of H2PO2 on the reduced Ce0.899M0.111O1.785(111) (M = Ti, Zr) surface. (August 2022) - Jia, Huiling; Jia, Ru; Shao, Qi; Wu, Jinxiu; Tan, Xin; Ren, Yuan
Abstract: To study the effect of Ti and Zr doping on the reducibility of CeO2 (111) substrate and the adsorption of H2 PO2 on KDP surface, the O vacancy formation energy of Ti/Zr-doped CeO2 (111) surface was calculated using DFT+ U method. The adsorption energy, bonding structure and local electronic structure of H2 PO2 on Ti/Zr-doped CeO1.963 (111) surface was analyzed. The results showed that the O vacancy formation energy of Ti/Zr-doped CeO2 (111) surface was reduced and the surface magnetic moment was enhanced. P-O and O-O covalent bonds were formed at the adsorption interface between H2 PO2 and the substrates. The adsorption energies of H2 PO2 on the reduced substrates were Ce0.899 Ti0.111 O1.963 (111) > CeO1.963 (111) > Ce0.899 Zr0.111 O1.963 (111). The adsorption energies of H2 PO2 on the substrates containing subsurface O vacancy were greater than those on the substrates containing surface O vacancy. The most stable adsorption site of H2 PO2 on the Ce0.899 Ti0.111 O1.963 (111)-sub surface was Oh site, P was bonded with two surface O, and the adsorption energy (7.612 eV) was the maximum, therefore, the Ce0.899 Ti0.111 O1.963 (111)-sub surface was the more suitable for polishing H2 PO2 on KDP surface. These results may lead to a better understanding and improving for the Ti/Zr-doped CeO2 polishing powder. Graphical Abstract: ga1